Optimasi Penjadwalan Produksi Injection Mould Base Frypan Handle Menggunakan Metode Algoritma Genetika - Fitri Annisa; Rina Sandora; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - Scheduling is an important aspect in the company to manage the length of production process time so as not to experience delays. Moulding Company is a manufacturing industry company with a production flow of job shop. The company's scheduling system on the manufacture of Injection Mould Base Frypan Handle is delayed where there is a non-achievable duration between actual production and planned production, to be able to obtain a solution to this problem, the proposed method, namely the Genetic Algorithm. The Genetic Algorithm method was chosen because this method does not have special criteria found in other heuristic algorithms, so the computation time is relatively shorter. Calculations on the Genetic Algorithm method using Microsoft Excel and MATLAB R2016a media. The calculation of the Genetic Algorithm method produces the optimal job operation flow, namely : 6-17-7-21-15-24-23-14-1-8-10-22-18-11-20-2-13-16-5-19-4-12-9-3. In addition, costs of Genetic Algorithm method decreased by 44% or Rp. 3,401,891, - more economical than company scheduling.